Development of vibrotactile sensory feedback for prosthetic hand user - Mohamad Hanif, Noor Hazrin Hany; Chappell, Paul H.; White, Neil M.; Cranny, Andy (2014)
Executing daily chores with missing limbs is undoubtedly very challenging. For a person who has lost his lower arm, it is highly desirable to replace this loss with a device that not only identical in appearance, but closely mimics its capabilities. While there are many prosthetic products of multiple functionalities in the current market, the capability of the device to replicate the tactile sensory system are often neglected. This research looks into supplementing a vibrotactile sensory feedback to the residual arm of prosthetic hand users. Surface information obtained at the fingertip of the prosthetic device becomes the input signals to the haptic actuator in generating vibration output. An Eccentric Rotation Mass (ERM) miniature motor has proven its capability to produce the required vibration in 2-axis direction within frequency bandwidth that matches the mechanoreceptor of the human skin. These findings are a stepping-stone in creating a real tactile sensation for prosthetic users.